Land & identity - Berberich, Christine,Campbell, Neil,Hudson, Robert (Rodopi, 2012)
Preliminary Material – Acknowledgements – Notes on Contributors – Framing and Reframing Land and Identity /Christine Berberich , Neil Campbell and Robert Hudson – Landscape, Land and Identity: A Performative Consideration /David Crouch – Nature Qua Identity: Nature, Culture and Relational Integrity /Fran Speed – The Geopolitical Picturesque /Donna Landry – Eschatological Landscape /Kirby Farrell – Cities Under a Sky of Mud: Landscapes of Mourning in Holocaust Texts /Jenni Adams – “This Time and Now”: Identity and Belonging in the Irish Diaspora: The Irish in Britain and Second-Generational Silence /Moy McCrory – “And I found myself looking through another window at a darker landscape inhabited by neither the present nor the past”: Recovering Identity in A Month in the Country /Elsa Cavalié – Beyond the Gaps: Postmodernist Representations of the Metropolis /Monica Germanà – “It is always another world”: Mapping the Global Imaginary in William Gibson’s Pattern Recognition /Brian Jarvis – The Shore is Not a Beach /Alex Lockwood – Lines of Flight: Unframing Land, Unframing Identity – Two Speculations /Christine Berberich and Neil Campbell – Index. This collection of essays aims to investigate the complex issues surrounding contemporary cultural discourses on land and identity – their production, construction, and reconstruction across a range of different texts and materials. The chapters offer disciplinary and trans-disciplinary approaches opening up discussion and new routes for research in a number of interrelated areas such as Countryside vs. City, Diaspora, Landscapes of Memory and Trauma, Migrational Spaces, and Ecology. They represent a number of innovative contemporary responses to how concepts of land intersect and dialogue with notions of identity across and between regions, nations, races, and cultures. Through employing interdisciplinary methods and theories drawn from diverse sources, such as cultural studies, spatial theory, philosophy and literary theory, the chapters chart varied and complex themes of identity formation in relation to spatiality
10.1163/9789401207430
Keywords: Electronic books; Human geography; Human ecology; Landscapes; Landscapes; Social aspects; Conference papers and proceedings